2018
DOI: 10.1007/s13197-018-3434-1
|View full text |Cite
|
Sign up to set email alerts
|

Degradation kinetics of anthocyanin and physicochemical changes in fermented turnip juice exposed to pulsed UV light

Abstract: In this study, the effects of pulsed UV (PUV) light on the degradation kinetics of anthocyanins and physicochemical properties of turnip juice were investigated. PUV light was applied to turnip juice at 3 different distances (5, 8, 13 cm) from the quartz window of the xenon lamp for 5 different times (5, 15, 30, 45, 60 s). The pH, total acidity (% lactic acid), monomeric anthocyanin content, color density, hue, brightness, and percent color components (yellow, red, and blue) of turnip juice changed significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 33 publications
0
11
0
1
Order By: Relevance
“…Although a decrease in the color values with the storage time was evidenced in the present study, the maximum ΔE was 6.50 ± 0.66 at the end of the shelflife studies which was slightly higher than that of the distinct ΔE value given by Ohta and Roberstson (2007). No significant changes in color tone, color in- distance (Karaoglan et al, 2019). UV-processed shalgam showed comparable results to heat processing in terms of the microbiological and bioactive properties and higher sensory scores for the six-month storage.…”
Section: Lactococcus Lactis Subsp Cremorismentioning
confidence: 87%
See 1 more Smart Citation
“…Although a decrease in the color values with the storage time was evidenced in the present study, the maximum ΔE was 6.50 ± 0.66 at the end of the shelflife studies which was slightly higher than that of the distinct ΔE value given by Ohta and Roberstson (2007). No significant changes in color tone, color in- distance (Karaoglan et al, 2019). UV-processed shalgam showed comparable results to heat processing in terms of the microbiological and bioactive properties and higher sensory scores for the six-month storage.…”
Section: Lactococcus Lactis Subsp Cremorismentioning
confidence: 87%
“…The previous studies reported pulsed ultraviolet light (PUV) processing of shalgam with respect to inactivation of Candida inconspicua (Karaoglan et al, 2017), the degradation kinetics of anthocyanins (Karaoglan et al, 2019), UV processing with microbial inactivation, the estimation of changes in bioactive properties, and shelflife extension (Dogan, 2017), and ultrasonication (US) processing relative to the heat treatment (Irkilmez, 2017). Thus far, the HHP processing the HHP treatment of shalgam, preliminary studies were performed to determine the HHP treatment parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The PL‐based degradation of monomeric anthocyanins in fermented vegetable (turnip) juice was also attempted by the log‐linear model ( R 2 = .91 to .99) by Karaoglan et al. (2019), although it was not the best fit.…”
Section: Kinetic Models Applied In Fruit Juices During Pltmentioning
confidence: 99%
“…It contains black carrots, bulgur flour, turnip, Baker's yeast and rock salt. This beverage is purplish-red color due to black carrot content [16]. It is produced by lactic acid fermentation.…”
Section: Introductionmentioning
confidence: 99%